Prevalence of stunting and thinness among rural adolescents of Darjeeling district, West Bengal, India (Italian Journal of Public Health, 2010)
Background: The primary causes of undernutrition in India are its large population, socio-economicdifferences and inadequate access to health facilities. Nutritional assessments among adolescents areimportant as they are the future parents and constitute a potentially susceptible group. Studies on theassessment of nutritional status of adolescents are less in number and a National database has not yet beendeveloped. The present cross-sectional investigation evaluates the prevalence of undernutrition among ruraladolescents (10 years - 17 years) from Darjeeling District, West Bengal, India.Methods: The present investigation was conducted among 726 rural school-going adolescents (376 boys and350 girls) belonging to the Rajbanshi, Bengali Muslim and Bengali Caste communities. The nutritional statuswas assessed in terms of stunting (Height-for-age below 3rd percentile) and thinness (BMI-for-age below 5thpercentile).Results: The overall prevalence of stunting and thinness were found to be 46.6% and 42.4% respectively. Ahigh prevalence of stunting was found among boys (43.1%) and girls (50.3%) (p>0.05). The highestprevalence of stunting was observed among boys of 17 years (63.6%) and among girls of 15 years (70.0%).The overall mean BMI for girls was slightly higher than boys (16.8 ± 3.4 kg/m2 and 15.9 ± 2.1 kg/m2respectively). A higher prevalence of overall thinness was found among boys (53.1%) than girls (32.0%)(p
Keywords: adolescent; stunting; BMI; thinness; anthropometry; West Bengal; India